Nutritive Value of Oak Leaves in Sheep - Elahi, Mostafa Yousef (Pakistan Journal of Nutrition, 2010)
Oak (Quercus sp.) leaves and branches is an important source of forage in the north-west of Iran, during winter season, when the pasture herbages are not available, but the nutritive value of this forage is not well known. In this study nutritive value of three species of oak tree leaves: Quercus persica, Q. infectoria and Q. libani were assessed by chemical analysis and in situ method. The chemical composition (g/kg DM basis) of the above species, respectively were as follow; 951, 927, 946, Organic Matter (OM); 115, 92, 123, Crude Protein (CP); 532, 540, 512, Neutral Detergent Fiber (NDF); 317, 300, 331, Acid Detergent Fiber (ADF); 98, 103, 95, lignin (ADL); 78, 115, 104, total phenols; 73, 109, 100, Total Tannins (TT); 14, 15, 12, Condensed Tannin (CT) and 46, 87, 62, Hydrolysable Tannin (HT). Protein Precipitable Phenolics (PPP) were respectively 160, 190 and 230 (g/kg total phenols). Rumen liquor taken from three male Ghezel sheep was used to measure the in situ degradability characteristics of oak leaf. The soluble component (a), insoluble but fermentable fraction (b), the potential degradability (a+b) and the Effective Degradability (ED) were higher in Q. persica (p<0.01). There was a strong negative correlation between TT, HT and ED in sheep. The rank order of nutritive value, in terms of chemical composition and in situ degradability were as follows: Q. persica > Q. libani > Q. infectoria.